A STUDY OF LINGUISTIC FEATURES INTO SOME PERCEPTION VERBS IN ENGLISH AND THEIR VIETNAMESE EQUIVALENTS - PHAN THỊ NHƯ NGUYÊN (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This study attempts to reach a thorough understanding of the four perception verbs “to look, to see, to watch, to glance”. In the study, constrastive analysis is suggested to be the main method of the study. Besides, the study also uses qualitive and quantitive approaches that help to analyse the data in a reliable way. The data on perception verbs in English and Vietnamese are collected, described and analysed. Furthermore, this study is designed to investigate the four perception verbs in terms of their syntactic, semantic and pragmatic features. The most important and significant problem, the similarities and differences among the four perception verbs on the three aspects above have been mentioned in order to help learner have better use of these verbs in communication. In addition, their Vietnamese equivalents are collected and analyzed in this chapter. On the basis of the findings, some pedagogical implications of study consisting of some problematic situations and suggestions for teaching, learning and using the four perception verbs have been put forward. Finally, suggestions for further study are made for anyone that is interested in this problem to continue studying to perfect this research.